TRAINING ON THE METHODOLOGY OF TAFSIR AL-QUR'AN FOR MADRASAH TEACHERS TO STRENGTHEN MULTICULTURAL EDUCATION - An, Andri Nirwana; Mahmudulhassan, Mahmudulhassan; Muthoifin, Muthoifin; Waston, Waston; Prakoso, Sajiwo Tri; Salsabila, Fahreza Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research explores the impact of Tafsir methodology training on Madrasah teachers in enhancing multicultural education in Indonesia. The training aimed to equip educators with a deeper understanding of Quranic values that promote diversity, tolerance, and social harmony, enabling them to apply these values effectively in the classroom. Through experiential learning, teachers gained the skills to interpret and contextualize Quranic verses related to inclusivity, addressing contemporary issues in a diverse society. The results of the training revealed that teachers were highly engaged and capable of connecting Quranic teachings to real-world situations, fostering an environment where students appreciated differences and promoted peaceful coexistence. Additionally, the training enhanced teachers' ability to use contextual Tafsir, making Quranic teachings more relevant to students from various cultural and religious backgrounds. This research highlights the importance of integrating Tafsir methodology into religious education to strengthen moderate and inclusive Islamic teachings, contributing to the broader goal of national unity in a multicultural society. Future research could assess the long-term impact of this training, its applicability in other educational contexts, and the potential of digital platforms to disseminate such training across Indonesia.